14-Day Repeated Intraperitoneal Toxicity Test of Ivermectin Microemulsion Injection in Wistar Rats - Dong, Zhen; Xing, Shou-ye; Zhang, Ji-yu; Zhou, Xu-zheng (Frontiers in Veterinary Science, 2020)
To evaluate the safety of ivermectin microemulsion injection, 100 Wistar rats were injected intraperitoneally at 0.38 g/kg, 0.19 g/kg, and 0.1 g/kg for 14 days. The 14-day repeated toxicity test of ivermectin microemulsion injection was systematically evaluated by clinical observation, organ coefficient, haematological examination, clinical chemistry examination and histopathological examination. The results showed that no rats died during the test. At the initial stage of treatment, the rats in the high dose group had mild clinical reaction, which disappeared after 4 days. Clinical chemistry showed that the high dose of ivermectin microemulsion could cause significant changes in ALT and LDH parameters in male rats; high and medium doses could increase the liver coefficients of male and female rats. The toxic target organ may be the liver as indicated by histopathological findings. No significant toxic injury was found in the heart, liver, spleen, lung, kidney, brain, ovary and testes of all groups of rats. No drug-related toxic effects were found at low doses, and thus the NOVEL of ivermectin microemulsion injection was 0.19 g/kg.